Assessment of biosafety training and practices in biomedical laboratories in Kinshasa, Democratic Republic of the Congo - Gamani, Diane Sare; Matimada, Gertrude Mongila; Masika, Lydie Hamunaki; Cyanga, Placide Ngandu; Mazoba, Tacite Kpanya; Muwonga, Jérémie Masidi (Orapuh Journal, 2025)
Introduction In biomedical laboratories, biosafety is a key element for preventing infections and ensuring the safety of healthcare workers and the community. In resource-limited settings like Kinshasa, Democratic Republic of the Congo (DRC), the status of biosafety training and practices among laboratory personnel remains unclear.PurposeThis study aimed to assess the training, practices, and satisfaction related to biosafety among laboratory personnel in biomedical laboratories in Kinshasa.MethodsA cross-sectional descriptive and analytical study was conducted between November 2024 and February 2025 in 56 laboratories in Kinshasa. A convenience sample of 290 laboratory staff members was interviewed using a structured questionnaire. Data were analysed with IBM SPSS 24.0, and associations were explored using Chi-square, Fisher’s exact, and logistic regression tests.ResultsThe majority of respondents were male (57.2%) and under 40 years of age (54.2%). Only 55.5% had received formal biosafety training, and among them, 34.8% had received the training over two years ago. Hepatitis B vaccination coverage was 30%. Overall satisfaction with biosafety management was low (27.6%). Biosafety training was significantly associated with older age (p = .032), longer work experience (p = .008), and hepatitis B vaccination (p < .001). Trained staff were more likely to be vaccinated (OR = 3.5) and to report satisfaction with biosafety measures (OR = 3.6).ConclusionBiosafety training and hepatitis B vaccination coverage remain insufficient among laboratory personnel in Kinshasa, with low levels of satisfaction regarding biosafety measures. Strengthening biosafety through regular training, provision of adequate equipment, and vaccination campaigns is urgently needed.